A rapid and simple clonality assay for bovine leukemia virus-infected cells by amplified fragment length polymorphism (AFLP) analysis - Tomoko Kobayashi; Sakurako Makimoto; Nagaki Ohnuki; Md Belal Hossain; M. Ishrat Jahan; Misaki Matsuo; Kazuhiko Imakawa; Yorifumi Satou (Microbiology Spectrum)
ABSTRACT Enzootic bovine leukosis (EBL), although eradicated in some European countries, is still the most common neoplastic disease of cattle, caused by the bovine leukemia virus (BLV). During the progression of EBL, BLV-infected cells clonally expand, and some of which result in tumor onset. The clonality of BLV-infected cells is generally evaluated with NGS or Sanger sequencing. Although these methods clearly distinguish EBL from non-EBL cases, the procedures are complex and not practical for routine veterinary diagnosis. In this study, we developed an amplified fragment length polymorphism (AFLP) analysis for BLV clonality assay (BLV-AFLP). This analysis uses restriction enzyme digestion to amplify the chimeric regions of BLV 3’ linear transcribed region (LTR) and host genome through conventional polymerase chain reaction (PCR) and visualizes the results by gel-electrophoresis. The method was established using cattle samples representing different stages of the disease: BLV-uninfected, non-EBL, and EBL cattle. Non-EBL cattle showed smeared bands, indicating polyclonal proliferation, while EBL cattle showed distinct bands, indicating clonal expansion. The results of BLV-AFLP correlated well with those of previously reported methods, suggesting its efficacy in detecting clonal proliferation. The validation using blood samples of non-EBL cattle and tumor samples of EBL cattle confirmed that BLV-AFLP could effectively identify clonal proliferation in EBL samples. Moreover, the emergence of dominant clones in the tumor at later stages was successfully detected before EBL onset in some cattle, highlighting its sensitivity and potential for early detection. Overall, BLV-AFLP is suitable for practical use in the field, improving BLV management strategies and minimizing economic losses.IMPORTANCEEnzootic bovine leukosis (EBL) is routinely diagnosed based on external manifestations at the farm, such as the presence of tumors and/or general lymph node enlargement. However, due to the nonspecific clinical manifestations of EBL, over half of EBL cases are unrecognized at the farm, with most cases being diagnosed during postmortem inspection at the slaughterhouse. Early detection and monitoring of clonal expansion are necessary for managing EBL and reducing economic losses. In this study, we developed BLV-AFLP that represents a significant advancement in the diagnosis of EBL in cattle. This method can rapidly assess the clonal proliferation of BLV-infected cells, crucial for distinguishing between asymptomatic and EBL cattle. Additionally, tracking clonal dynamics offers insights into the disease’s progression, potentially providing strategies for avoiding economic losses. Overall, as BLV-AFLP is a simple and rapid test for detecting EBL, it is feasible and efficient for routine veterinary practice.